The Antioxidant Procyanidin Reduces Reactive Oxygen Species Signaling in Macrophages and Ameliorates Experimental Colitis in Mice - Chen, Lu; You, Qian; Hu, Liang; Gao, Jian; Meng, Qianqian; Liu, Wentao; Wu, Xuefeng; Xu, Qiang (Frontiers in Immunology, 2018)
Management of inflammatory bowel disease (IBD) is a real clinical challenge. Despite intense investigation, the mechanisms of IBD remain substantially unidentified. Some inflammatory conditions, such as matrix metalloproteinases (MMPs) and the nuclear factor-κB (NF-κB) and NOD-Like receptor protein 3 (NLRP3) inflammasome signalling pathways, are reported to contribute to the development and maintenance of IBD. Regulation of their common upstream signalling, that is, reactive oxygen species (ROS), may be important to control the progression of IBD. In the present study, we found that procyanidin, a powerful anti-oxidation flavonoid, has a significant effect on ROS clearance on THP-1 macrophages after LPS or LPS-combined ATP stimulation, thus down-regulating MMP9 expression, suppressing NF-κB signalling and interrupting the formation of the NLRP3 inflammasome. Moreover, our in vivo data showed that procyanidin attenuated DSS-induced experimental colitis in a dose-dependent fashion by suppressing the expression of MMP9, NF-κB and NLRP3 inflammasome signalling in colonic tissues in mice. Overall, our results suggested that targeting ROS could be a potential therapeutic choice for colonic inflammation.